Evaluation of sensitivities and specificities of SARS-CoV detection by real-time quantitative reverse transcription-PCR assays - Xu, Li-li (Virol Sin, 2009)
The etiological agent of severe acute respiratory syndrome (SARS) was identified as a new coronavirus, termed SARS-CoV. Establishment of an efficient and sensitive diagnostic system of SARS-CoV genetic materials is crucial for SARS control. In this study, we quantified SARS-CoV mRNAs in both infected cell culture lysate and in supernatant by using Real-time quantitative revere transcription-PCR based on EvaGreen™ dye and Taqman-MGB probes. For extensive evaluation of sensitivities and specificities, 13 pairs of primers and 4 probes were designed based on different genes of SARS-CoV. Glyceraldehydes-3-phosphate dehydrogenase (GAPDH) was selected as the internal control gene. Results showed that S-gene-specific PCR was the most sensitive for detection, but because of its sequence variability in the different viral strains, primers and a probe based on the N gene were suitable substitutions. Meanwhile, we found the mRNA concentrations in cell culture lysates were much higher than in cell supernatant and facilited more sensitive detection of the SARS-CoV.